Point Shear‐Wave Elastography Using Acoustic Radiation Force Impulse Imaging for the Prediction of Liver‐Related Events in Patients With Chronic Viral Hepatitis. Issue 1 (12th November 2020) - Hernandez Sampere, Lisa; Vermehren, Johannes; Mücke, Victoria T.; Graf, Christiana; Peiffer, Kai‐Henrik; Dultz, Georg; Zeuzem, Stefan; Waidmann, Oliver; Filmann, Natalie; Bojunga, Joerg; Sarrazin, Christoph; Friedrich‐Rust, Mireen; et al.
Abstract : Chronic viral hepatitis is associated with substantial morbidity and mortality worldwide. The aim of our study was to assess the ability of point shear‐wave elastography (pSWE) using acoustic radiation force impulse imaging for the prediction of the following liver‐related events (LREs): new diagnosis of HCC, liver transplantation, or liver‐related death (hepatic decompensation was not included as an LRE). pSWE was performed at study inclusion and compared with liver histology, transient elastography (TE), and serologic biomarkers (aspartate aminotransferase to platelet ratio index, Fibrosis‐4, FibroTest). The performance of pSWE and TE to predict LREs was assessed by calculating the area under the receiver operating characteristic curve and a Cox proportional‐hazards regression model. A total of 254 patients with a median follow‐up of 78 months were included in the study. LRE occurred in 28 patients (11%) during follow‐up. In both patients with hepatitis B virus and hepatitis C virus (HCV), pSWE showed significant correlations with noninvasive tests and TE, and median pSWE and TE values were significantly different between patients with LREs and patients without LREs (both P < 0.0001). In patients with HCV, the area under the receiver operating characteristic curve for pSWE and TE to predict LREs were comparable: 0.859 (95% confidence interval [CI], 0.747‐0.969) and 0.852 (95% CI, 0.737‐0.967) ( P = 0.93). In Cox regression analysis, pSWE independently predicted LREs in all patients with HCV (hazard ratio, 17.9; 95% CI, 5.21‐61‐17; P < 0.0001) and those who later received direct‐acting antiviral therapy (hazard ratio, 17.11; 95% CI, 3.88‐75.55; P = 0.0002). Conclusion: Our study shows good comparability between pSWE and TE. pSWE is a promising tool for the prediction of LREs in patients with viral hepatitis, particularly those with chronic HCV. Further studies are needed to confirm our data and assess their prognostic value in other liver diseases. Abstract : Chronic viral hepatitis is associated with substantial morbidity and mortality worldwide. Our study shows good comparability of point shear wave elastography (pSWE) and transient elastography. pSWE is a promising tool for the prediction of liver‐related events in patients with viral hepatitis, particularly in patients with cHCV.